Bulky hinge bracelet: inspired by Malaysia batik sarung / Wan Nur Ain Amirah Wan Azmi - Wan Azmi, Wan Nur Ain Amirah (2022)
The Traditional batik sarong in Malaysia represents the continuity of tradition and change with multiple cultural resonances.